A Comparative Study Of Some Health Dimensions For Middle School Students Through Practicing The Physical And Physical Education Class - Ben Chaib, Ahmed (sports creativity, 2025)
The purpose of this research is to compare some of the health dimensions of middle school students through practicing the physical education and sports class. Where the researcher used the descriptive comparative approach, and the study sample consisted of (100) students, then it was chosen by the random method, and the researcher used the mental health scale in the test of persistence, endurance, flexibility, strength, and body composition. Moreover, the study found: There are statistically significant differences in the level of dimensions, according to the age variable and in favor of the older group, by gender and in favor of males, according to the type of activity and in favor of individual activities